Comparison of the levelized cost and thermoeconomic methodologies – Cost allocation in a solar polygeneration plant to produce power, desalted water, cooling and process heat. (15th July 2018) - Leiva-Illanes, Roberto; Escobar, Rodrigo; Cardemil, José M.; Alarcón-Padilla, Diego-César
Highlights: A comparison of the levelized cost and thermoeconomic methodologies is performed. A polygeneration plant is configured to generate electricity, fresh water, cooling, and heat. The thermoeconomic method is a more equitable and rational cost allocation method. The levelized cost method is a simpler and faster method than thermoeconomic method. The lowest unit specific costs occur at the same sizing of solar field and thermal storage. Abstract: The present work shows a comparison between the levelized cost and the thermoeconomic methods in their application to assess the performance of a solar polygeneration plant. The aim is to analyze the costs allocation process, the unit specific costs of each product, as well as the energy and exergy efficiencies, which allows to identify the main advantages of both the evaluated methods. The methodology is applied in a case study configured by a concentrated solar power with thermal energy storage and backup system, combined to a multi-effect distillation plant, an absorption refrigeration plant, and a process heat module. The present study reveals that through the levelized cost method, the cost associated to the electricity generation is higher than it is by applying the thermoeconomic method, whereas the costs of water, cooling and process heat are significantly lower. Those differences represent an increase of about 35.1% in the case of the electricity, and a reduction in the cost associated to the water, cooling, and heat production by around 34.4%, 78.1%, and 97.6%, respectively. Results show that the thermoeconomic method is an equitable and rational cost allocation method which is suitable for a solar polygeneration plant. This method is recommended when a more precise analysis is required to assess the proper costs of different products, and for assessing the benefits of a polygeneration plant, when compared to stand-alone plants. However, the levelized cost method is a simple and fast method, and a deep knowledge of thermodynamics is not required, being recommended when in need to perform a first approach of the costs of each product.